Aplicação da metodologia do Design Thinking e a ferramenta Business Model Canvas em uma empresa de etiquetas - Komoto, Marcio Hidenobu (2019)
Brazil has been undergoing constant changes in the economic scenario, directly affecting the Brazilian market and especially micro and small companies. These changes and instabilities usually bring a high mortality rate of the organizations, so that this does not occur, managers are seeking means for the survival of their companies. This work aimed to elaborate a methodology for the creation of a new innovative business model that will help the organization grow and survive in the Brazilian market. We used the Thinking Design mentality, which encourages the creative process and the generation of ideas, and the Business Model Canvas tool, a resource that helps business management. Among the results of the study, we obtained insight cards that supported the creation of ideas; later, prototypes of business models were elaborated from these ideas, which were analyzed and studied through a SWOT matrix, having as conclusion and main result the creation of a new business model for the company studied in this work.